Minimising convex combinations of low eigenvalues∗. (7th April 2014) - Iversen, Mette; Mazzoleni, Dario
<x content-type="archive" xml:space="preserve">Abstract</x> We consider the variational problem inf{αλ1(Ω) + βλ2(Ω) + (1 − α − β)λ3(Ω) | Ω open in ℝn, |Ω| ≤ 1}, for α, β ∈ [0, 1], α + β ≤ 1, where λk(Ω) is the kth eigenvalue of the Dirichlet Laplacian acting in L2(Ω) and |Ω| is the Lebesgue measure of Ω. We investigate for which values of α, β every minimiser is connected.